Half-time in the European Parliament—Expectations, reality, outlook - Rudolf Hrbek (Intereconomics, 1982)
The European Parliament was set up by direct elections in June 1979. Great expectations had been placed in these direct elections with regard to the further development of the European Community. Now, half-way through the Parliament's five-year term, a certain Euro-weariness is gaining ground. Had expectations been pitched too high? How is the work of the European Parliament so far to be assessed? What are the prospects for the future?
Keywords: 330; EC